AYRANCI BERENDİ SNOW PIER CHEESE - AKTURFAN , Mustafa; ŞEN, Ali (SSD Journal, 2023)
Cheese is a dairy product obtained by processing milk. Cheese making begins with the processing of milk. Next, the milk is fermented and coagulated. The clot is separated from the liquid part and shaped and matured by various methods. Cheese can have different tastes, textures, smells, and appearances. Some cheeses are salty, some are bitter, and some are sweet. Cheeses are also rich in protein, calcium, and other nutrients. There are many traditional cheese varieties in Turkey. Traditional products reflect the culture of that region by identifying with the geography where they emerged. Nowadays, it is seen that traditional products are being forgotten due to reasons such as developing technology and the intensity of business life. Traditional products must be registered with a geographical indication in order to transfer them to future generations. Geographical indication product is a system that secures the producer and the consumer. Ayrancı Berendi Snow Pit Cheese, which is produced by the local people with traditional methods in the Karaman Ayrancı district, is a product that should be evaluated as a candidate for geographical indication. This research was carried out in order to determine the production method and distinctive features of Ayrancı Berendi Snow Pit Cheese and to evaluate it within the scope of geographical indication. The qualitative research method was preferred in the study. Face-to-face interviews were held with people who produce Berendi Snow Pit Cheese in Ayrancı district and villages of Karaman province. Research data were evaluated using the descriptive analysis method. At the end of the research; It has been determined that Ayrancı Berendi Snow Pit Cheese has been produced by the local people for a long time with traditional methods, sheep’s milk is used in its production, the cheese has a unique mold flora, and is matured in the Berendi Snow Pit. The cheese appears to be snow whitish and reddish in color with the effect of the cave.